ڕەوڕەوەى ڕەنگەکان لە شیعرى گۆران - كريم, ظاهر طيف; فؤاد, نيان نوشيروان (Sulaimani Journal for Humanities, 2000)
This study is an attempt to clarify Goran's poetic effectivity. His poem “The far away Hope” is , as an artistic tablean , Composed of a number of effective connected circular images. These circles the senses of perceptive Seeing , hearing smelling and touching represent the main color in the tablear , which interplay with the sub-colors to conform the whole image. The basic motive behind these circles is the profound sensitivity and great talent of the poet , which provided the poem with effectivity and vividy.